FUNGSI MANAJEMEN PUSKESMAS DALAM PROGRAM PEMBERIAN ASI EKSKLUSIF (STUDI KUALITATIF DI WILAYAH KERJA PUSKESMAS SUMBERAGUNG) - Maria Retno Ambarwati; Teta Puji Rahayu; Tutiek Herlina (JURNAL PENELITIAN KESEHATAN, 2016)
Coverage of exclusive breastfeeding in Magetan in the year 2013 is 75.66%. Puskesmas Sumberagung have low exclusive breastfeeding coverage that is 54.66%. The aims of this study was to describe management functions in exclusive breastfeeding programs in Puskesmas Sumberagung that can explains the consider factor to overcome the failure of exclusive breastfeeding, especially in terms of health care management.This study was a phenomenological qualitative study, used purposive sampling method. This studi used 7 research subject’s, namely the Head of Puskesmas, Nutrition Programmers, Midwife Coordinator, 4 midwife’s. Data collected by in depth interview technique and observation. The tools used are notes and tape recorder. Data were analyzed with qualitative analysis and presented based on the conclusion of the data collected. Based on the results, the workforce who carry out program activities exclusive breastfeeding was less; not maximal operational activities program exclusive breastfeeding was likely due to the availability of funds lacking; infrastructure implementation program of exclusive breastfeeding in the Puskesmas is not complete yet; specific planning on breastfeeding does not exist; breastfeeding program is not considered a priority yet; the team does not have a breastfeeding counselor; 10 Steps to Successful Breastfeeding not completed carry out yet; implementation of monitoring, control, communication and motivation are lacking. Overall evaluation of the program conducted in a mini workshop to look at the minimum service standard is achieved or not and no reporting system.It is advisable to establish a breastfeeding counselor team who have been trained, develop relevant planning program exclusive breastfeeding in detail, develop facilities and infrastructure implementation program of exclusive breastfeeding in the health center, and take advantage of the aid already received. Improved functions of monitoring, control, communication and motivation are lacking. Keywords: management functions, exclusive breastfeeding